Design and Analysis of Electric Power-assisted Variable Transmission Ratio Steering System for Sweeper - Dandan Chen; Zhijian Su; Yuzhuang Guo (Jixie chuandong)
Aiming at the current application of electric power steering in medium-sized sweepers， in order to solve the problem of oversized motors and difficult applications， a new design scheme of variable transmission ratio transmission is proposed. Taking the electric power steering system of a certain model as an example， the transmission scheme of the steering gear used by the vehicle and the change of the output torque of the motor are studied. The mathematical model of the steering system is established， and the variable transmission ratio design parameters of rack and pinion are determined in combination with the operating conditions of the cleaning vehicle， and the calculation and contrastive analysis are carried out， the improvement effect of the scheme is verified. The new design scheme can directly reduce the output torque variation range of the assisted motor， reduce the selected motor power value， achieve the purpose of reducing the size of the motor， expanding the scope of application of the electric power steering system， and saving energy.